“Project for a Spatiotemporal Neuroscience” – Brain and Psyche Share Their Topography and Dynamic - Northoff, Georg; Scalabrini, Andrea (Frontiers in Psychology, 2021)
What kind of neuroscience does psychoanalysis require? At his time, Freud in his “Project for a Scientific Psychology” searched for a model of the brain that could relate to incorporate the psyche’s topography and dynamic. Current neuropsychoanalysis builds on specific functions as investigated in Affective and Cognitive (and Social) Neuroscience including embodied approaches. The brain’s various functions are often converged with prediction as operationalized in predictive coding (PC) and Free energy principle (FEP) which, recently, have been conceived as core for a “New Project for Scientific Psychology”. We propose to search for a yet more comprehensive and holistic neuroscience that focuses primarily on its topography and dynamic analogous to Freud’s model of the psyche. This leads us to what we describe as “Spatiotemporal Neuroscience” that focuses on the spatial topography and temporal dynamic of the brain’s neural activity including how they shape affective, cognitive, and social functions including PC and FEP (first part). That is illustrated by the temporally and spatially nested neural hierarchy of the self in the brain’s neural activity (second and third part). This sets the ground for developing our proposed “Project for a Spatiotemporal Neuroscience”, which complements and extends both Freud’s and Solms’ projects (fourth part) and also carries major practical implications as it lays the ground for a novel form of neuroscientifically informed psychotherapy, namely “ Spatiotemporal Psychotherapy”. In conclusion, “Spatiotemporal Neuroscience” provides an intimate link of brain and psyche by showing topography and dynamic as their shared features, i.e., “common currency”.